Changes in the prevalence of overweight, obesity, and severe obesity between 2010 and 2017 in preschoolers: A population‐based study. Issue 11 (18th July 2019) - Ball, Geoff D.C.; Savu, Anamaria; Kaul, Padma
Summary: We evaluated changes in overweight, obesity, and severe obesity in a population of 4‐ to 6‐year‐olds from 2010 to 2017. Anthropometric data were collected during children's preschool immunization visits in Edmonton and Calgary, Alberta, Canada. Body mass index (BMI), BMI z scores, and weight status categories were based on the World Health Organization criteria. Across 8 years, we examined population‐level data from 161 114 children in which the prevalence of overweight (17.8%‐15.7%; P < .001) and obesity (4.7%‐4.2%; .004) decreased, while severe obesity (2.4%‐2.2%; .3) remained unchanged. Overweight decreased in both boys (19.2%‐16.8%; P < .0001) and girls (16.4%‐14.6%; .003); obesity decreased in boys (5.3%‐4.4%; .005), but not girls (4.1%‐3.9%; .2). Severe obesity was stable in both sexes. Annual household income and breast feeding had positive, but variable moderating effects on overweight and obesity exclusively. Overall, reductions in overweight and obesity were positive findings, but targeted strategies are needed to reduce severe obesity in preschoolers.